PERKEMBANGAN MASA PRANATAL - Nurul Fara Atika; Angel lofersia; Rahil Maryam; Linda Yarni (Komunitas Menulis dan Meneliti (Kolibi), 2023)
Prenatal development is the initial development of humans. Starting from the growth that occurs from the meeting of mature sperm cells which will eventually become new cells and form a zygote. This fertilization indicates the proper functioning of the human reproductive organs. This research aims to explain the characteristics of the prenatal period and the prenatal development period. Prenatal development research methods involve a series of scientific approaches to understand and analyze the development of the embryo and fetus from the beginning of intrauterine life. Based on the discussion above, it can be concluded that in prenatal development there are several ways to determine a person's life, which can be seen from psychology, namely that life begins reacting to external stimuli, while biological life begins at conception or fertilization, namely egg cells and spermatozoa cells. The two cells that have united grow and develop in the female reproductive organs. The prenatal period is the period of life of the fetus in the womb.